The great cat massacre : and other episodes in French cultural history - Darnton, Robert (Basic Books, 2009)
When the apprentices of a Paris printing shop in the 1730s held a series of mock trials and then hanged all the cats they could lay their hands on, why did they find it so hilariously funny that they choked with laughter when they reenacted it in pantomime some twenty times? Why in the eighteenth-century version of Little Red Riding Hood did the wolf eat the child at the end? What did the anonymous townsman of Montpelier have in mind when he kept an exhaustive dossier on all the activities of his native city? These are some of the provocative questions Robert Darnton answers in this classic work of European history in what we like to call “The Age of Enlightenment.”